The determinants of compensation report transparency: manager incentives and firm characteristics - Iris Pfeiffer; Svenja Jarchow (Journal of Business Economics, 2023)
This paper analyses the determinants of disclosure in compensation reports. Using a hand-collected dataset of 429 observations we assess which compensation, governance and ownership variables influence the quality of disclosure in compensation reports from 2006 to 2014 in a German setting. Managers have incentives to conceal compensation disclosure leading to a conflict of interest with shareholders. The overall findings suggest that opportunistic reporting incentives, as proposed by the managerial power theory, cannot explain a lack of more detailed disclosure. Managers rather avoid these disclosures because they would require additional effort. The empirical analyses reveal four major disclosure determinants: company size, age, family members in the boards and verticality. Other variables such as proprietary costs, governance variables and performance show no or no stable influence. The absence of disclosure is therefore a confluence of company resources (company size and forecasts increase disclosure), owner interests (family members in the board decreases disclosure), and concerns about social equity infringement (higher pay inequity leads to lower disclosure).
Keywords: G30; J33; M12; M52; 650; Executive compensation; Excessive compensation; Compensation disclosure; Corporate governance